Ben behind his voices : one family's journey from the chaos of schizophrenia to hope - Kaye, Randye (Rowman & Littlefield, 2011)
The author, Ben's mother, provides an account of his experiences with schizophrenia, describing Ben from his childhood through his turbulent teenage years before his diagnosis, and discussing the struggles and challenges faced by Ben's family in their efforts to provide support to Ben throughout the stages of his illness.